INVESTMENT TRADING SYSTEM USING PT JALEN WITH MICROSOFT VISUAL FOXPRO 9.0 - Januar Al Farisi; Ristyawati, SKom, MMSI Ristyawati, SKom, MMSI (Jurnal Sistem Informasi, 2009)
The development of increasingly advanced technology, especially computers, have now entered a wide range of existing activities, advantages of the use of computer technology is characterized by speed, precision, and accuracy, as well as ensuring that data will be stored. The author conducted a study on investment trading system that is used in PT Jalen, diamana in its data processing still using manual system. This system has the disadvantage of consuming much time and energy making it less effective. From these circumstances, the authors intend to provide an alternative in the processing of customer data, traders, and investment is no longer manually but with the aim of facilitate the computerized administrator and trader in performing its duties, and also speed up customer service. Storage of all data related to the investment trading system are stored in a database that is well designed so that it can provide the required information accurately.